Upaya Guru PPKN dalam Meningkatkan Sikap Jujur Siswa - Hidayati Suhaili; Syafwan Syafwan (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of this study was to determine the efforts of PPKn teachers in improving students' honest attitudes and what obstacles were encountered by teachers in improving students' honest attitudes at SMPN 3 Payakumbuh District. The type of research used is qualitative with descriptive method. The results of this study are: 1) PPKn teachers' efforts in improving students' honest attitudes are: (a) Providing learning motivation for students; (b) Provide various learning models; (c) Reduction of value when caught cheating on the results of a friend's test; (d) Assign error points weights; (e) The imposition of punitive sanctions. 2) The teacher's obstacle factors in improving students' honest attitudes are: (a) Factors from within the students; (b) The interest of students in learning is low; (b) Lack of understanding of students in applying an honest attitude; (c) Factors from outside the students, such as the teacher's busyness and environmental factors. The conclusion that the PPKn teacher's efforts in increasing honesty in students is to always instill and increase honesty in themselves. Keywords: Honest Attitude, PPKN Teacher.